Demographic Studies of Autopsied Cases at North Bengal Medical College Hospital During the National Lockdown Period Due to COVID 19 Pandemic - Vivek Kumar; Jagadish Biswas; Tenzing ZampelBhutia; Dibyakar Chhetri; Rumi Maitra; Prabir Kumar Deb (Institute of Medico-legal Publications Pvt Ltd, 2021)
The outbreak of COVID 19 pandemic in India has started from the month of March when many cases weretested positive for novel coronavirus. The high infectivity of the disease led many governments to imposestrict lockdown with the aim of limiting its spread. To restrict its spread and save the people of India ourgovernment has also imposed strict nationwide lockdown in a phase wise manner. Though the lockdown wasimposed to restrict the spread of COVID 19 but it had severe undesirable impact on the socio-economicaland psychological status of the people especially of low to medium income groups involved in private jobs.The aim of this study was to study the cases of autopsied unnatural deaths with special emphasis to find outthe correlation between demographic pattern of deceased with the lockdown. In this study we have analysedthe 961 cases of autopsied unnatural deathsin the mortuary of Department of Forensic Medicine, NBMCH,Darjeeling, West Bengal from the first day of lockdown up to the month of September (24th March 2020 toSeptember 2020). All data were analysed by appropriate statistical tolls like SPSS software. In this study wefound that male (66.4%) predominated over the females and most of the cases belongs to adult age group(44.27%). Persons involved in private jobs (44%) were more severely affected compared to the governmentjobs and cases of suicidal deaths (45.7%) rises but cases of deaths due to road traffic accidents (13.9%)drastically reduced during lockdown period.